Vitamin-D Deficiency and Hashimoto’s Thyroiditis-Myth or Reality - Rasool, Hira; Waheed, Zubair; Siddiqi, Fuad Ahmad; Tareen, Tariq Bashir; Khattak, Abdul Latif; ., Imran (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the comparison between vitamin D deficiency and Autoimmune Thyroid Disease, especially Hashimoto’s Thyroiditis. Study Design: Cross-sectional Study. Place and Duration of Study: Department of Medicine, Combined Military Hospital, Rawalpindi Pakistan, from June 2022 to July 2023. Methodology: In this study, 400 subjects of both genders, between the age of 20-70 years, were enrolled. All the patients who reported for thyroid evaluation at medical Outpatient Department, Combined Military Hospital, Rawalpindi were included in this research. Individuals with renal or hepatic diseases, primary hyperparathyroidism, metabolic bone diseases, epilepsy, subacute thyroiditis, transitory thyroid dysfunction with negative thyroid autoantibodies, and missing lab data were excluded. All the individuals were tested for serum vitamin D, phosphorus, parathyroid hormone, calcium, thyroid function tests including antithyroid antibodies. Vitamin D deficiency and insufficiency were indicated as serum 25(OH)D level <25nmol/L and 25-75nmol/L, respectively. Results: When compared to 110(27.5%) individuals without autoimmune thyroid disease, 290(72.5%) /patients with Autoimmune Thyroid Disease had a higher rate of vitamin D insufficiency (85.3% vs. 55.5%, p=0.001). There was a significant inverse correlation between serum vitamin D levels and serum thyroid-stimulating hormone levels when gender, BMI, age, and sample season were taken into consideration. Conclusion: Deficiency of vitamin D has a strong correlation with Hashimoto’s Thyroiditis and Autoimmune Thyroid diseases. High blood serum levels of Thyroid stimulating hormone have an independent correlation with decreased levels of vitamin D.